Peran Produk Rahn Dalam Penguatan Usaha Untuk Meningkatkan Pendapatan Nasabah di Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Kramat Cabang Jatiarjo Kecamatan Prigen Pasuruan - Mundir, Abdillah; Fatimah, Dian (Widya Balina, 2021)
Abstract: Financial institutions have a role as intermediary institutions or a process of transferring funds from savers to borrowers or those who need funds. The role of financial institutions is very large in the growth and development of the community's economy. Currently, non-bank financial institutions also have the influence to develop the businesses of the surrounding community that cannot be reached by banks. One of them is in the Sharia Savings and Loans Cooperative (KSPPS) Kramat, which provides financing with rahn products. Researchers conducted research on the implementation of rahn products and strengthening the business of members in KSPPS Kramat. The purpose of this study was to determine the application of Rahn products and to determine the effect of Rahn financing in increasing income and strengthening businesses that were built or even being run by members. The research conducted at KSPPS Kramat uses qualitative research methods, by interviewing several members of KSPPS Kramat and their administrators. While the data collection techniques carried out by researchers are interviews, documentation and observation. In this study the researchers found several things. In the application of the Rahn product at KSPPS Kramat using a sale and purchase agreement, but it does not take advantage of the goods that are pawned and the application for financing is also easy. With the financing of rahn products, businesses around the village of Jatiarjo have increased, this is because the installments at KSPPS Kramat do not have usury. And the monthly installments are quite light, making it easier for the community to pay off the proposed financing. Keywords: KSPPS, Rahn Products, Income Increase.